Dynamics of illegal deforestation in eleven years in the state of Pará-Brazil (Research, Society and Development, 2022)
The objective of this work is to show the dynamics of deforestation that occurred on properties in the state of Pará, based on public data from the List of Illegal Deforestation of the State of Pará - LDI for the years 2009 to 2019 and to emphasize the five municipalities that have the highest number of deforested area. Data such as spreadsheets and the areas of the municipalities and their deforestation characteristics were extracted from the page of the secretary of environment and sustainability of the state of Pará – SEMAS/PA. For the making of the map, centroids were created from the Shapefile files of polygons of the properties available on the SEMAS/PA portal, for the construction of a shape with all the deforestation points of the LDI, from these points, the function of Heat Map or Kernel Map in the Qgis 3.10 software corunã, to characterize and densify the areas where the points or areas with deforestation are concentrated. As for the number of hectares deforested by municipality, the municipalities of Altamira, São Felix do Xingú, Novo Progresso, Itaituba and Prainha lead the list in this eleven-year period. The highest concentration of properties with embargoed areas according to LDI data are found in the municipalities of Altamira, São Félix do Xingu, Novo Progresso, Monte Alegre, Prainha and Itaituba.